Modulation of the Keap1/Nrf2/HO-1 signaling axis by ferulic acid and hesperidin in the mitigation of cyclophosphamide-induced nephrotoxicity: In vivo and in silico approaches - Mazin M.T. Shigidi; Mahrous A. Ibrahim; Farooq A. Wani; Enas M.A. Mostafa; Athar M. Khalifa; Noha M. Abd El-Fadeal; Rania A. Galhom; Zinab A. Ali; Nermeen M. Nooreldien; Dina H. El-Sheikh; Osama S. Elserafy (Tissue and Cell, 2026)

Innovative effect of pomegranate peel extract nanoemulsion in diarrheic lambs: Prospective towards promoting immunity, hematology indices, antioxidant competence, and controlling Escherichia coli infection - Doaa Ibrahim; Marwa I. Abd El-Hamid; Ahmed Abdelfattah‑Hassan; Aya Sh. Metwally; Asmaa A. Azouz; El Shymaa A. Abdallah; Basma Badawy; Rania M.S. El-Malt; Saqer S. Alotaibi; Sherief Mohamed Abdel-Raheem; Ahmed I. El Sheikh; Eman Metwally (The Veterinary Journal, 2026)

Genomic and in Vitro Evaluation of Probiotic Traits in a Gut-Derived Bacillus cereus PX472023 from Farmed Lates Calcarifer, Asian Seabass - Amulya S G; Gayatri Tripathi; Samad Sheikh; R Bharathi Rathinam (Marine Biotechnology, 2026)

Probiotics, Psychobiotics, Paraprobiotics, and Postbiotics in Gut-Brain Axis Modulation: Multi-Omics and AI-Driven Precision Nutrition for Cognitive Health - Ibrahim S. I. Al-Adham; Ahmed S. A. Ali Agha; Mayyas Al‐Remawi; Faisal Al‑Akayleh; Ahmed Al-Sheikh; Faisal Aburub; Phillip J. Collier (Probiotics and Antimicrobial Proteins, 2026)

Tea for two: India’s commodity agroforests as coexistence landscapes for the endangered Asiatic wild dogs and people - Abraham Pious; Anshita Das; H. S. Thasmai; Divyajyoti Ganguly; Avantika Deep Sharma; Sabiya Sheikh; Arjun Srivathsa (Ambio, 2026)

Compositional zoning, crystal chemistry and metamorphic growth of monazite in the Greater Himalayan Sequence, Dhauliganga Valley, Garhwal Himalaya - Chandni Chaurasia; Satyajeet S. Thakur; Suresh C. Patel; Nainika Gour; Janisar M. Sheikh (Geochemistry, 2026)

Holocene–pleistocene provenance transitions in the Cauvery Delta, South India: Evidence from Sr-Nd isotopes - Malik Zubair Ahmad; Pramod Singh; S. Balakrishnan; Suhail Hussain Sheikh (Chemical Geology, 2026)

Multiscale Representative Elementary Volume Determination in Complex Porous Media: An Integrated Hydrodynamic and Thermodynamic Modelling Approach - Shaheryar T. Hussain; Klaus Regenauer-Lieb; Aleksandr Zhuravljov; Sheikh S. Rahman (Transport in Porous Media, 2026)
Understanding fluid transport in microporous media remains a complex challenge due to the intricate interplay of heterogeneity and scale-dependent behaviours. This study introduces a novel multiscale discretisation framework, specifically tailored for dual-porosity systems, and integrates it with an enhanced multiphase solver to determine representative elementary volumes (REVs) across contrasting pore structures. The proposed numerical approach incorporates a hybrid formulation combining two-phase Darcy flow for macro-scale domains with Navier–Stokes and volume-of-fluid (VOF) interface tracking for micro-scale regions. This enables simulation of complex immiscible flows with explicit resolution of both macro- and microporous pathways. A dedicated mesh refinement strategy ensures computational efficiency while preserving geometric fidelity across porosity scales. We apply this framework to two carbonate samples: the Savonnieres carbonate and the Mount Gambier limestone. In the Savonnieres sample, REV convergence could not be achieved even at the largest available micro-CT volume (1000 3 voxels, ~ 3.8 mm 3 ) due to pronounced microstructural clustering. In contrast, the Mount Gambier limestone exhibited stable hydrodynamic and thermodynamic REV behaviour above 1200 3 voxels (~ 3.21 mm 3 ), closely matching experimental core-scale estimates. These findings reinforce the robustness of the proposed methodology and underscore its potential for broader application to microporous media with diverse heterogeneity profiles.

Dual protection by naringin and dexrazoxane against iron-induced erythrocyte damage: Exploring their synergistic regulation of ferroptosis and eryptosis - Gamaleldin I. Harisa; Ahmed H. Bakheit; Amsha S. Alsegiani; Sheikh F. Ahmad; Sabry M. Attia (Journal of Trace Elements in Medicine and Biology, 2026)

Development of a Gellan–Carbopol in Situ Gel System for Intranasal Delivery of Artemether-Loaded SLNs: Optimization and Kinetic Evaluation - Harish Bhute; Pramod S. Salve; Sameer Sheikh; Ujban Md Hussain; Samiksha Tammewar; Amol A. Tatode; Mohammad Qutub; Tanvi Premchandani (Journal of Pharmaceutical Innovation, 2026)

Exploration of zileuton protective mechanisms against vancomycin-associated nephrotoxicity - Cole S. Hudson; James E. Smith; Rongjin Sun; Linh T. Vuong; Luan D. Truong; David Sheikh-Hamad; Masayuki Nigo; Ming Hu; Vincent H. Tam (Toxicology and Applied Pharmacology, 2025)

An investigation into awareness, attitudes, and factors influencing the acceptance of rainwater harvesting systems from the perspective of the academic community in Iran - V. Sheikh; S. P. Nainiva; M. Mohammadrezaei (International Journal of Energy and Water Resources, 2025)

Mechanistic insights of plant–microbe interactions for enhancing the growth and productivity of plants under salt stress conditions for agricultural sustainability - Babita Sharma; Rajeshwari Negi; S. Renuka Jyothi; Anirudh Gupta; Samiksha Jhamta; Neelam Yadav; Narinderpal Kaur; Paridhi Puri; Samrendra Singh Thakur; Subhikshaa Bagavathiappan; Neelam Thakur; Sheikh Shreaz; et al. (Physiology and Molecular Biology of Plants, 2025)

Anode substrate tailoring in fed-batch photosynthetic microbial desalination cell for industrial and domestic wastewater treatment - S. S. Ali; Z. Sheikh; W. Miran; Z. Ullah (International Journal of Environmental Science and Technology, 2025)

Benefits of fenugreek extract on renal tissue of ovariectomized rats treated with gentamicin: Biochemical, gene expression, and histopathological assessments - Sawsan M.A. El-Sheikh; Mohamed Gomaa; Randa Saied; Mohamed M.M. Metwally; Heba H. Mahboub; Hanan M. Alharbi; Aaser M. Abdelazim; Hanim S. Heikal; Tarek Khamis; Azza Galal (Tissue and Cell, 2025)

First Report on Development of Liquid Microbial Consortium for Plant Growth Promotion of Flax (Linum usitatissimum L.) Growing in Indian Himalayan Regions - Rajeshwari Negi; Babita Sharma; S. Renuka Jyothi; Anirudh Gupta; Neelam Yadav; Narinderpal Kaur; Paridhi Puri; Sangram Singh; Ashutosh Kumar Rai; Sheikh Shreaz; Ajar Nath Yadav (Current Microbiology, 2025)

A coupled adsorption-photo-Fenton process of ZnFe2O4/rGO nanocomposite optimized for efficient dye degradation - Madhuri S. Patil; Arif D. Sheikh; Kiran Kumar K. Sharma (Journal of Water Process Engineering, 2025)

Assessing the impact of various nanoparticles on physiological parameters of in vitro generated broccoli (Brassica oleracea var. italica) plants - Muzamil Yousuf; Gurdev Chand; Neha Sharma; Zahid Ayoub Bhat; Zahid Nabi Sheikh; Dalia Fouad; Farid S. Ataya (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Synergistic Effect of Calcium and Boron on Apple cv. ‘Oregon Spur’: Enhancing Quality and Extending Shelf Life - Zahid Ayoub Bhat; Mahital Jamwal; Nirmal Sharma; Zahid Nabi Sheikh; Neha Sharma; Dalia Fouad; Farid S. Ataya; Haziq Shabir (Applied Fruit Science, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

A comprehensive review on the neuropharmacological effects of Phoenix dactylifera and the potential role of its phenolic constituents - Md Mohaiminul Islam; Razina Rouf; Jamil A. Shilpi; Bassem Yousef Sheikh; Mohammad S. Mubarak; Shaikh Jamal Uddin (Food Bioscience, 2025)

Retraction Note: Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Uranium removal from environmental water and nuclear waste: Nanomaterial solutions and their environmental sustainability - Ahmed S. Helal; Miryana Hémadi; John S. Lomas; Souad Ammar; Ali Abdelhafiz; Said M. El-Sheikh; Sheta M. Sheta; Mitchell Galanek; Mohamed H. Hassan; Jeng-Kuei Chang; Ju Li (Chemical Engineering Journal, 2025)

Assessing smog trends and sources of air pollutants across northeastern districts of Punjab, Pakistan using geospatial techniques - M. A. Goheer; S. S. Hassan; A. S. Sheikh; Y. Malik; M. Uzair; T. N. Satti (International Journal of Environmental Science and Technology, 2025)

Synergistic effects of methyl jasmonate and salicylic acid enhances photosynthetic efficiency in drought-stressed French beans - Mohammed Mohi-Ud-Din; Mahmudul Hasan Tahery; Anika Nazran; Dipa Talukder; Md. Mehedi Hasan; S. M. Zubair Al-Meraj; Sheikh Faruk Ahmed (South African Journal of Botany, 2025)

Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Neuroprotective effect of red dragon fruit extract ameliorates oxidative stress and inflammation in D-galactose-induced aging rat model: biochemical, histological and immunohistochemical study - Manar Fouli Gaber Ibrahim; Fatma F. Ali; Sayed Fouad El-Sheikh Ali; Emad S. Shaker; Hemdan I. Mahmoud; Fatma ElZahraa Mohammed Abdellatif; Sahar A. Mokhemer (Journal of Molecular Histology, 2025)

Effect of low doses of gamma radiation on cell growth over an electrospun polycaprolactone/zinc acetate scaffold for biomedical applications - Naglaa M. Ismail; Soheir Korraa; M. B. S. Osman; Eman El Sheikh (Biophysical Reviews, 2025)

High-resolution Danian–Selandian benthic foraminifera-based paleoenvironmental reconstruction and response to sequence stratigraphy: Inferences from the Elles section, El Kef Basin, Tunisia - Sherif Farouk; Islam El-Sheikh; Sreepat Jain; Fayez Ahmad; Zaineb Elamri; Jenö Nagy; Khaled Al-Kahtany; Youssef S. Bazeen (Marine Micropaleontology, 2025)

Gene expression profiling of indigenous Tharparkar and crossbred Vrindavani cattle affected with lameness using PBMC model - Amit Baranwal; Sheikh Firdous Ahmad; Ravi Kumar Gandham; C. S. Celus; Gyanendra Kumar Gaur (Tropical Animal Health and Production, 2024)

Molecular Regulator Driving Endometriosis Towards Endometrial Cancer: A Multi-Scale Computational Investigation to Repurpose Anti-Cancer drugs - S. Mahema; Jency Roshni; Janaki Raman; Sheikh F. Ahmad; Haneen A. Al-Mazroua; Shiek S. S. J. Ahmed (Cell Biochemistry and Biophysics, 2024)

Unlocking Nature’s Stress Reliever: The Role of Melatonin in Enhancing the Resilience of Fruit Crops Against Abiotic Stress - Susmita Shil; Shubranil Das; Michi Tani; Jome Rime; Sumit Sow; Songthat William Haokip; Kh. Anush Sheikh; Mangalam S. Bhargava; Onam Pertin; Siddhartha Singh (Applied Fruit Science, 2024)

Impact of Clinical Trial Design on Recruitment of Racial and Ethnic Minorities - Saad Sheikh; Debora S. Bruno; Yilun Sun; Victoria Deng; Shearwood McClelland; Elizabeth Obi; Valerie Vinson; April Firstencel; Bob Lanese; Loretta Lausin; Jennifer A. Dorth; Nicholas G. Zaorsky; et al. (Journal of Cancer Education, 2024)

Aquaporin mediated silicon-enhanced root hydraulic conductance is benefit to cadmium dilution in tobacco seedlings - Zhiguo Liu; Lei Hou; Jiyuan Yan; Parvaiz Ahmad; Mengzhan Qin; Runze Li; Mohamed A. El-Sheikh; Rupesh Deshmukh; Sreeja S. Sudhakaran; Basharat Ali; Li Zhang; Long Yang; et al. (Journal of Hazardous Materials, 2024)

Introgression of 1RSWR.1BL translocation, Bx7OE and stripe rust resistance genes in bread wheat cultivars - Sheenu Garg; Ambika Sharma; Satinder Kaur; H. S. Dhaliwal; Pritesh Vyas; Imran Sheikh (Cereal Research Communications, 2024)

Planktic foraminifer response and paleoceanographic changes across the Danian – Selandian interval in the southern Tethys (Elles section, Central Tunisia) - Youssef S. Bazeen; Sherif Farouk; Zaineb Elamri; Fayez Ahmad; Khaled Al-Kahtany; Amr S. Zaky; Islam El-Sheikh (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Classic and alternative disinfection practices for preventing of hospital-acquired infections: a systemic review - J. Sheikh; T. T. Swee; S. Saidin; S. A. Malik; L. S. Chua; M. T. F. Thye; L. K. Meng; M. Kun (International Journal of Environmental Science and Technology, 2024)

Palladium and platinum complexes based on pyridine bases induced anticancer effectiveness via apoptosis protein signaling in cancer cells - Mohamed M. El-bendary; Abdullah Akhdhar; Abdullah S. Al-Bogami; Doaa Domyati; Abdulaziz A. Kalantan; Faisal Ay Alzahrani; Samer M. Alamoudi; Ryan A. Sheikh; Ehab M. M. Ali (BioMetals, 2024)

Characterization of Gold-Enhanced Titania: Boosting Cell Proliferation and Combating Bacterial Infestation - Touseef Amna; M. Shamshi Hassan; Jari S. Algethami; Alya Aljuaid; Anas Alfarsi; Rasha Alnefaie; Faheem A. Sheikh; Myung-Seob Khil (Tissue Engineering and Regenerative Medicine, 2024)

The vegetation around the foothills of the Hijaz Mountains, Saudi Arabia - Nick Hofland; Mohamed Z. Hatim; Jacob Thomas; John A. M. Janssen; Awad S. Alharti; Ahmed H. Alfarhan; Abdulrahman A. Alatar; Joop H. J. Schaminée; Mohamed A. El-Sheikh (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)
Despite Saudi Arabia being an interesting area from a floristic perspective, its vegetation is still relatively poorly studied. This certainly applies to the Hijaz Mountains and adjacent coastal zones. We aim to describe the flora and vegetation of the foothills of the Hijaz Mountains regarding the environmental conditions. Hijaz Mountains and adjacent coastal zones, Saudi Arabia. We studied the vegetation at the Hijaz Mountains’ foothills along two transects of vegetation surveys, one along the coast and one more inland. In addition, soil samples were taken and analyzed for soil texture, pH, electrical conductivity, organic matter, calcium carbonate and the concentration of the elements N, Na, K, Ca, Mg, Fe and Mn were determined. We calculated the data clustering tendency (Hopkins’ test analysis) and its optimal number of clusters (Elbow method). We used modified TWINSPAN to cluster the data and validated the resulting communities using the Silhouette algorithm. Seven plant communities resulted, each one dominated by a different plant species, namely: Haloxylon salicornicum , Lycium shawii , Senegalia hamulosa , Vachellia tortilis , Zygophyllum coccineum , Vachellia flava and Stipagrostis plumosa , and were described based on their floristic composition and could be further grouped into three vegetation clusters. The communities had varying ranges of occurrence in the study area, some dominating certain sections, with latitude and altitude being the biggest distinguishing environmental variables between the communities. We present a description of the vegetation of the Hijaz Mountains foothills. Our study is considered an important basis for decision-making of nature conservation and in-depth surveys of the area. Graphic abstract

Introgression of recombinant 1RSWW.1BL without secalin and with Glu-B3/Gli-B1 into elite wheat cultivars through marker-assisted backcross breeding - Ambika Sharma; Satinder Kaur; Monika Garg; Rajesh Kumar; B. S. Khatkar; Pritesh Vyas; H. S. Dhaliwal; Imran Sheikh (Cereal Research Communications, 2024)

Development of southern corn leaf blight (SCLB) resistant and high-popping volume composite popcorn using phenotypic and marker-assisted selection (MAS) - Shivani Thakur; Rahul Kumar; Baldeep Singh; Yogesh Vikal; H. S. Dhaliwal; Vikrant Tyagi; Imran Sheikh (Cereal Research Communications, 2024)

Status and long-term changes of coral reefs around Zanzibar - Ali M. Ussi; Mohammed S. Mohammed; Rashid J. Rashid; Mohammed A. Sheikh; Peter A. Staehr; Christopher A. Muhando; Saleh Yahya; Karsten Dahl (Frontiers in Marine Science, 2024)
Introduction Coral reefs as key ecosystems in Zanzibar are exposed to several anthropogenic and natural stressors. Methods The benthic composition and coverage of coral reefs were investigated on three data sets involving ten coral reefs monitored from 1992 to 2016. Firstly, we investigated differences in the reef composition using data from seven reefs in 2015. Secondly, we analyzed communities on three distinctive reefs (2010 to 2012) to understand the importance of seasons and reef zones (slope, crest and flat) on species abundance. Finally, we investigated long-term changes (1992 to 2016) of five reefs. Results Branching Porites and Acropora , and soft coral order Corallimorpharia, characterized sheltered reef communities. Soft corals and algal species characterized the reef communities exposed to strong hydrodynamic conditions, which also displayed greater cover of rocks and rubbles. The average dissimilarity between reefs ranged between 60% and 75%. The seasonal changes in community structure for reefs near Stone Town were mostly associated with soft coral Corallimorpharia. Indeed, the bare rock and algae distinguished the northern exposed reef from more sheltered reefs. Acropora was a key genus for the sheltered Chumbe reef, which explained between 14% and 18% of the dissimilarities among the three reefs. Hard corals covered between 40% and 70% in most years, with severe declines following El Niño events in 1998 and 2016. The dominating genus Acropora showed a strong decline from the late 1990s’ with signs of recovery at remote reefs compared to reefs closer to human residence. Discussion Our results highlight the importance of seasonality and spatial differences, reflecting differences in human impact and physical exposure and significant long-term changes in coral communities. Continued monitoring of reef health is essential to evaluate the success of ongoing management to sustain the reef services.

Marker-assisted selection for scab resistance and columnar growth habit in inter-varietal population of apple (Malus × domestica) - Aatifa Rasool; K. M. Bhat; M. A. Mir; A. S. Sundouri; Salha Mesfer ALshamrani; Abeer S. Aloufi; Diaa Abd El Moneim; Sheikh Mansoor; Yong Suk Chung (Plant Biotechnology Reports, 2024)

Biochemical study of the effect of mesenchymal stem cells-derived exosome versus l-Dopa in experimentally induced Parkinson’s disease in rats - Asmaa S. Mohamed; Dina S. Abdel-Fattah; Ghada A. Abdel-Aleem; Thanaa F. El-Sheikh; Manal M. Elbatch (Molecular and Cellular Biochemistry, 2023)
Parkinson’s disease (PD) is a chronic and ongoing neurological condition. Unfortunately, as the dopaminergic terminals continue to deteriorate, the effectiveness of anti-Parkinson therapy decreases. This study aimed to examine the effects of BM-MSCs-derived exosomes in rats induced with Parkinson’s disease. The goal was to determine their potential for neurogenic repair and functional restoration. Forty male albino rats were divided into four groups: control (group I), PD (group II), PD- l -Dopa (group III), and PD-exosome (group IV). Motor tests, histopathological examinations, and immunohistochemistry for tyrosine hydroxylase were performed on brain tissue. The levels of α-synuclein, DJ-1, PARKIN, circRNA.2837, and microRNA-34b were measured in brain homogenates. Rotenone induced motor deficits and neuronal alterations. Groups (III) and (IV) showed improvement in motor function, histopathology, α-synuclein, PARKIN, and DJ-1 compared to group (II). Group (IV) showed improvement in microRNA-34b and circRNA.2837 compared to groups (III) and (II). MSC-derived exosomes showed a greater suppression of neurodegenerative disease (ND) compared to l -Dopa in Parkinson’s patients. Graphical abstract

Polyethylene glycol embedded reduced graphene oxide supramolecular assemblies for enhanced room-temperature gas sensors - Ahmad Umar; Rajesh Kumar; Pravin S. More; Ahmed A. Ibrahim; Hassan Algadi; Mohsen A. Alhamami; Sotirios Baskoutas; Sheikh Akbar (Environmental Research, 2023)

Genetic analysis of iron, zinc and grain yield in wheat-Aegilops derivatives using multi-locus GWAS - Harneet Kaur; Prachi Sharma; Jitendra Kumar; Vikas Kumar Singh; Neeraj Kumar Vasistha; Vijay Gahlaut; Vikrant Tyagi; Shailender Kumar Verma; Sukhwinder Singh; H S Dhaliwal; Imran Sheikh (Molecular Biology Reports, 2023)

TAS2R38 bitter taste perception in the Koṅkaṇī Sārasvata Brahmin population - Jaison Jeevan Sequeira; Sheikh Nizamuddin; George van Driem; Mohammed S. Mustak (Genes & Genomics, 2023)

Self-assembled Gallic acid loaded lecithin-chitosan hybrid nanostructured gel as a potential tool against imiquimod-induced psoriasis - Sahim Aziz Hazari; Afsana Sheikh; Mohammed A.S. Abourehab; Alaa S. Tulbah; Prashant Kesharwani (Environmental Research, 2023)

Novel approach to the stability assessment of reinforced concrete columns - S. Mahdi; M.S. Mohamed Ali; A.H. Sheikh; R.J. Gravina (Engineering Structures, 2023)

VIV and forced convection response of a freely oscillating cylinder to a single impulse perturbation of varying intensity - Asad Ijaz; S. Manzoor; M. Ebrahem; E. Uddin; N.A. Sheikh (Ocean Engineering, 2023)

Pore-Scale Evaluation of Physicochemical Interactions by Engineered Water Injections - Artur Shapoval; Aleksandr Zhuravljov; Zakhar Lanetc; Sheikh S. Rahman (Transport in Porous Media, 2023)
Engineered water injections have gained a lot of interest as an economic and effective method of improving the oil recovery. However, the complexity of the physicochemical interactions between the brines of various compositions, oil and rock has led researchers to provide multiple ways to explain this phenomenon. In this work, we evaluate the previously suggested mechanisms, namely wettability alteration and emulsification, against high-resolution micro-CT coreflood observations in a limestone sample. This is achieved by integrating the effects of above-mentioned mechanisms into a volume-of-fluid simulation by using geochemical modelling and experimental measurements. This has allowed us to explain the effect of capillary force affecting mechanisms, whereby we were able to achieve 6% increase in recovery factor. We have also observed that these mechanisms have limitation in improving recovery due to fingering and subsequent formation of the stagnation zones inside the core samples. When viscous effect is considered in numerical study, 22% increase in recovery is achieved by reorientation of the main flow paths and mobilisation of the previously unconnected oil clusters. This result is closer to 24% increase in recovery factor which was observed in experimental study and signifies that viscosity increase due to emulsification is an important mechanism of engineered water injections.

Cytological, biochemical and molecular characterization of Triticum-Aegilops amphiploids - Ramandeep Kaur; Harneet Kaur; Pooja Saini; Vikrant Tyagi; Naseer Ahmed; H. S. Dhaliwal; Imran Sheikh (Journal of Plant Biochemistry and Biotechnology, 2023)

Nutritional value and end-use quality of durum wheat - Pooja Saini; Harneet Kaur; Vikrant Tyagi; Pawan Saini; Naseer Ahmed; H. S. Dhaliwal; Imran Sheikh (Cereal Research Communications, 2023)

Genetic enhancement of nutritional and end-use quality in bread wheat through alien introgressions from wild relatives - Pooja Saini; Harneet Kaur; Vikrant Tyagi; Ajar Nath Yadav; Pawan Saini; Varruchi Sharma; Charan Singh; H. S. Dhaliwal; Imran Sheikh (Cereal Research Communications, 2023)

Interactive adverse effects of low-density polyethylene microplastics on marine microalga Chaetoceros calcitrans - Hoda H. Senousy; Hanan M. Khairy; Heba S. El-Sayed; Eman R. Sallam; Mohamed A. El-Sheikh; Mostafa E. Elshobary (Chemosphere, 2023)

Corrigendum: The microbiome of Suaeda monoica and Dipterygium glaucum from southern Corniche (Saudi Arabia) reveals different recruitment patterns of bacteria and archaea - Rewaa S. Jalal; Hassan I. Sheikh; Mohammed T. Alotaibi; Ashwag Y. Shami; Ruba A. Ashy; Naseebh N. Baeshen; Aala A. Abulfaraj; Lina Baz; Mohammed Refai; Nabih A. Baeshen; Anis Fadhlina; Mohammed Arifullah; et al. (Frontiers in Marine Science, 2022)

Comparative transcriptomics unravels new genes imparting scab resistance in apple (Malus x domestica Borkh.) - Khalid Z. Masoodi; Nazeer Ahmed; Mudasir A. Mir; Basharat Bhat; Afshana Shafi; Sheikh Mansoor; Rovidha S. Rasool; Mifftha Yaseen; Zahoor A. Dar; Javid I. Mir; Syed Mudasir Andrabi; Nazir A. Ganai (Functional & Integrative Genomics, 2022)

Sustainability of the grazing and feeding resources for sheep during the non-migratory period in Jammu and Kashmir - Sheikh Shubeena; Abdul Hai; S. A. Hamdani; A. H. Akand; Insha Amin; Subata Mahboob; Shiasta Seedat-Un Nissa; Shahzada Mudasir Rashid (Tropical Animal Health and Production, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Integrating blue: How do we make nationally determined contributions work for both blue carbon and local coastal communities? - Amrit Melissa Dencer-Brown; Robyn Shilland; Daniel Friess; Dorothée Herr; Lisa Benson; Nicholas J. Berry; Miguel Cifuentes-Jara; Patrick Colas; Ellyn Damayanti; Elisa López García; Marina Gavaldão; Gabriel Grimsditch; et al. (Ambio, 2022)
Blue Carbon Ecosystems (BCEs) help mitigate and adapt to climate change but their integration into policy, such as Nationally Determined Contributions (NDCs), remains underdeveloped. Most BCE conservation requires community engagement, hence community-scale projects must be nested within the implementation of NDCs without compromising livelihoods or social justice. Thirty-three experts, drawn from academia, project development and policy, each developed ten key questions for consideration on how to achieve this. These questions were distilled into ten themes, ranked in order of importance, giving three broad categories of people , policy & finance , and science & technology . Critical considerations for success include the need for genuine participation by communities, inclusive project governance, integration of local work into national policies and practices, sustaining livelihoods and income (for example through the voluntary carbon market and/or national Payment for Ecosystem Services and other types of financial compensation schemes) and simplification of carbon accounting and verification methodologies to lower barriers to entry.

Biosorption of Uranium from aqueous solution by green microalga Chlorella sorokiniana - Mohamed A. Embaby; El-sayed A. Haggag; Ahemd S. El-Sheikh; Diaa A. Marrez (Environmental Science and Pollution Research, 2022)
Uranium and its compounds are radioactive and toxic, as well as highly polluting and damaging the environment. Novel uranium adsorbents with high biosorption capacity that are both eco-friendly and cost-effective are continuously being researched. The non-living biomass of the fresh water green microalga Chlorella sorokiniana was used to study the biosorption of uranium from aqueous solution. The biosorption of uranium from aqueous solutions onto the biomass of microalga C. sorokiniana was investigated in batch studies. The results showed that the optimal pH for uranium biosorption onto C. sorokiniana was 2.5. Uranium biosorption occurred quickly, with an equilibrium time of 90 min. The kinetics followed a pseudo-second-order rate equation, and the biosorption process fit the Langmuir isotherm model well, with a maximum monolayer adsorption capacity of 188.7 mg/g. The linear plot of the DKR model revealed that the mean free energy E = 14.8 kJ/mol, confirming chemisorption adsorption with ion exchange mode. The morphology of the algal biomass was investigated using a scanning electron microscope and energy dispersive X-ray spectroscopy. The FTIR spectroscopy analysis demonstrated that functional groups (carboxyl, amino, and hydroxyl) on the algal surface could contribute to the uranium biosorption process, which involves ion exchange and uranium absorption, and coordination mechanisms. Thermodynamic simulations indicated that the uranium biosorption process was exothermic (ΔH = −19.5562 kJ/mol) and spontaneous at lower temperatures. The current study revealed that C. sorokiniana non-living biomass could be an efficient, rapid, low-cost, and convenient method of removing uranium from aqueous solution.

GC–MS Analysis and In Vitro Evaluation of Antioxidant and Cytotoxic Activities of Melaleuca viminalis (Myrtaceae) - Ahmed G. Darwish; Hanaa M. Hassan; Mamdouh Nabil Samy; Emad S. Shaker; Sheikh Mehboob Basha; Subramani Paranthaman Balasubramani (Journal of Plant Biochemistry and Biotechnology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Microbiome of Suaeda monoica and Dipterygium glaucum From Southern Corniche (Saudi Arabia) Reveals Different Recruitment Patterns of Bacteria and Archaea - Rewaa S. Jalal; Hassan I. Sheikh; Mohammed T. Alotaibi; Ashwag Y. Shami; Ruba A. Ashy; Naseebh N. Baeshen; Aala A. Abulfaraj; Lina Baz; Mohammed Refai; Nabih A. Baeshen; Anis Fadhlina; Mohammed Arifullah; et al. (Frontiers in Marine Science, 2022)
Soil and plant interact differently in response to the same stress (e.g., salinity) and recruit certain bacteria. The southern corniche (Saudi Arabia) has limited plant growth, which could be due to the high temperature and salinity. The study aimed to determine the soil microbiome of selected plants and the interactions between soil and these plants. Suaeda monoica and Dipterygium glaucum soil samples were collected from the crust (surface) and rhizosphere, while soil with no plant growth from the nearby area was used as control. High-throughput hypervariable V3–V4 region of the 16S rRNA gene was used to evaluate the shifts in soil microbiome due to growth of plant growth. The analysis detected up to 16% archaeal strains in S. monoica -associated samples, while D. glaucum and control samples contained 100% bacterial strains. The top 10 phyla composition of the soil samples were Proteobacteria, Actinobacteria, Firmicutes, Gemmatimonadota, Bacteroidota, Halobacterota, Cyanobacteria, Cloroflexi, Planctomycetota, and Myxococcota. The V3–V4 region analysis successfully clustered the 5 samples into 3 clusters (control, D. glaucum , and S. monoica ) at higher-order classification but not at the species level due to unidentified bacteria. The main differences between soil samples were due to halophyte S. monoica samples containing high amounts of halophilic archaea and halophilic bacteria. This showed that selected plants interacted differently with the soil. EC- and KO-based analyses of functional genes and pathways showed that 5 pathways were specific to control, 11 pathways were observed only in D. glaucum samples, 12 pathways were expressed in S. monoica samples only, and 9 pathways were common in all samples. The study also detected numerous relatively novel genera in high abundance such as Aliifodinibius , Pontibacter , and Lacunisphaera . This showed that the soil in the sampling area is not well explored and that novel species could be isolated from the soil samples and used for future research.

Supplementation with selenium nanoparticles alleviates diabetic nephropathy during pregnancy in the diabetic female rats - Ibrahim M. Alhazza; Hossam Ebaid; Mohamed S. Omar; Iftekhar Hassan; Mohamed A. Habila; Jameel Al-Tamimi; Mohamed Sheikh (Environmental Science and Pollution Research, 2022)

Introgression of Recombinant 1RSWR.1BL Translocation and Rust Resistance Genes in Bread Wheat cv. HD2967 Through Marker-Assisted Selection - Ambika Sharma; Imran Sheikh; Satinder Kaur; Pritesh Vyas; H. S. Dhaliwal (Plant Molecular Biology Reporter, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Screening the biochemical composition of some marine microalgal species for feeding Cyclops abyssorum divergens - Heba S. El-Sayed; Hoda H. Senousy; Aml Z. Ghoneim; Gihan M. El-Khodary; Mohamed A. El-Sheikh; Hanan M. Khairy; Salwa A. El-Saidy (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Molecular mapping of popping volume QTL in popcorn (Zea maize L.) - Shivani Thakur; Rahul Kumar; Yogesh Vikal; Pritesh Vyas; Imran Sheikh; H. S. Dhaliwal (Journal of Plant Biochemistry and Biotechnology, 2021)

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

Elucidating genetic divergence of silkworm (Bombyx mori) using internal transcribed Spacer1 (ITS1) - Asma S. Hakak; Malik Farooq; Zafar I. Buhroo; Mudasir A. Mir; Gowhar Ali; Firdos A. Nehvi; Nazeer Ahmed; Sheikh Mansoor; Khalid Z. Masoodi (International Journal of Tropical Insect Science, 2021)

Modeling the effect of chloride contaminant migration on groundwater - S. Elkholy; Mostafa Abd El-Warith; H. Guirguis; M. El-Sheikh (Innovative Infrastructure Solutions, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Changes in Shale Rock Properties and Wave Velocity Anisotropy Induced by Increasing Temperature - Yu Suo; Zhixi Chen; Sheikh S. Rahman (Natural Resources Research, 2020)

Introgression of powdery mildew resistance from Aegilops triuncialis into wheat through induced homeologous pairing - Robinsh Kamboj; Sushma Sharma; Rahul Kumar; Prachi Sharma; Vikas Kumar Ravat; Parveen Chhuneja; Pritesh Vyas; Imran Sheikh; H. S. Dhaliwal (Journal of Plant Biochemistry and Biotechnology, 2020)

Transfer of grain softness from 5U-5A wheat-Aegilops triuncialis substitution line to bread wheat through induced homeologous pairing - Yogesh Sharma; Imran Sheikh; Ambika Sharma; Ajar Nath Yadav; Krishan Kumar; Parveen Chhuneja; Sewa Ram; Sunil Kumar; Pritesh Vyas; H. S. Dhaliwal (Journal of Plant Biochemistry and Biotechnology, 2020)

Experimental and Numerical Investigation of the Effect of Bedding Layer Orientation on Fracture Toughness of Shale Rocks - Yu Suo; Zhixi Chen; Sheikh S. Rahman; Huifang Song (Rock Mechanics and Rock Engineering, 2020)

First report of Diplodia bulgarica a new species causing canker disease of apple (Malus domestica Borkh) in India - S. U. Nabi; W. H. Raja; J. I. Mir; O. C. Sharma; D. B. Singh; M. A. Sheikh; Nida Yousuf; D. Kamil (Journal of Plant Pathology, 2020)

Identification of dust generation potential in Mighan watershed - M. Fooladi; F. Ghadimi; S. J. Sheikh Zakariaee; H. Rahimpour Bonab (International Journal of Environmental Science and Technology, 2020)

Large-scale dynamics of western disturbances caused extreme precipitation on 24–27 January 2017 over Jammu and Kashmir, India - J. A. Para; Amit Kesarkar; J. Bhate; V. Singh; A. Panchal; A. Munsi; Y. Shivamurthy; S. Lotus; N. Ahmad; J. A. Sheikh (Modeling Earth Systems and Environment, 2020)

Chromium removal from tannery wastewater using Syzygium cumini bark adsorbent - Md. A. Hashem; Md. A. Momen; M. Hasan; Md. S. Nur-A-Tomal; Md. H. R. Sheikh (International Journal of Environmental Science and Technology, 2019)

Physiologic serum 1,25 dihydroxyvitamin D is inversely associated with prostatic Ki67 staining in a diverse sample of radical prostatectomy patients - Adrian Rosenberg; Oluwarotimi S. Nettey; Pooja Gogana; Ujalla Sheikh; Virgilia Macias; Andre Kajdacsy-Balla; Roohollah Sharifi; Rick A. Kittles; Adam B. Murphy (Cancer Causes & Control, 2019)

Diversity in wild relatives of wheat: an expedition collection from cold-arid Indian Himalayas - K. Pradheep; Mohar Singh; Sheikh M. Sultan; Kuldeep Singh; R. Parimalan; S. P. Ahlawat (Genetic Resources and Crop Evolution, 2019)

Tropical hilsa shad ( Tenualosa ilisha ): Biology, fishery and management - M. Shahadat Hossain; S. M. Sharifuzzaman; Muhammad Abdur Rouf; Robert S. Pomeroy; Md Delwer Hossain; Sayedur R. Chowdhury; Sheikh AftabUddin (Fish and Fisheries, 2019)
Tropical hilsa shad, which is an anadromous fish migrating from the sea to spawn in freshwater river, constitutes an important fishery in some Asian and Middle East countries, particularly in Bangladesh. But, historical information on hilsa biology and ecology has confronted the scientists and policymakers with research and management challenges. We have reviewed both the old and recent findings on hilsa fishery to document the status of knowledge and potential gaps, necessary to comprehend for formulating a more effective fishery management plan. Thus, there has been a decline in hilsa catches in the riverine system associated with shift in fish migration routes, indiscriminate harvesting of brood and juvenile fish, and degradation of habitat. Specifically, the riverine hilsa catches peaked in the 1960s, declining thereafter, and became relatively abundant in marine waters since 1990s. Biological data indicated that hilsa goes through multiple reproductive cycles; therefore, a comprehensive understanding of reproductive biology, recruitment by various cohorts, stock abundance and habitats across the life cycle are necessary to accurately impose fishery regulatory measures, such as fishing ban in spawning season in Bangladesh. Moreover, domestication initiative is important for artificial seed production and mariculture development of hilsa that can not only offer economic return to small‐scale farmers but also reduce the growing pressure on capture fishery. Importantly, the arrangement of co‐management is found ideal as fishermen, scientists and managers can work jointly to improve the regulatory processes and to sustain the hilsa fishery over time.

Correction to: A review on fisheries and conservation status of Asian horseshoe crabs - B. Akbar John; B. R. Nelson; Hassan I. Sheikh; S. G. Cheung; Yusli Wardiatno; Bisnu Prasad Dash; Keiji Tsuchiya; Yumiko Iwasaki; Siddhartha Pati (Biodiversity and Conservation, 2018)

A review on fisheries and conservation status of Asian horseshoe crabs - B. Akbar John; B. R. Nelson; Hassan I. Sheikh; S. G. Cheung; Yusli Wardiatno; Bisnu Prasad Dash; Keiji Tsuchiya; Yumiko Iwasaki; Siddhartha Pati (Biodiversity and Conservation, 2018)

Evaluation of end use quality and root traits in wheat cultivars associated with 1RS.1BL translocation - Ambika Sharma; Imran Sheikh; Rahul Kumar; Krishan Kumar; Pritesh Vyas; H. S. Dhaliwal (Euphytica, 2018)

Mining and characterization of EST-SSR markers for Zingiber officinale Roscoe with transferability to other species of Zingiberaceae - Praveen Awasthi; Ashish Singh; Gulfam Sheikh; Vidushi Mahajan; Ajai Prakash Gupta; Suphla Gupta; Yashbir S. Bedi; Sumit G. Gandhi (Physiology and Molecular Biology of Plants, 2017)

The landscape of genetic diseases in Saudi Arabia based on the first 1000 diagnostic panels and exomes - Dorota Monies; Mohamed Abouelhoda; Moeenaldeen AlSayed; Zuhair Alhassnan; Maha Alotaibi; Husam Kayyali; Mohammed Al-Owain; Ayaz Shah; Zuhair Rahbeeni; Mohammad A. Al-Muhaizea; Hamad I. Alzaidan; Edward Cupler; et al. (Human Genetics, 2017)

Selective recovery of chromium ions from waste tannery solution for preparation of chromium oxide nanoparticles - S. M. El-Sheikh; M. A. Rabah (International Journal of Environmental Science and Technology, 2015)

Ambient noise measurements in Rawalpindi–Islamabad, twin cities of Pakistan: a step towards site response analysis to mitigate impact of natural hazard - S. M. Talha Qadri; S. H. Sajjad; R. A. Sheikh; Khaista Rehman; Zahid Rafi; Bushra Nawaz; Waseem Haider (Natural Hazards, 2015)

Nociception and role of immune system in pain - Vivek Verma; Zeeshan Sheikh; Ahad S. Ahmed (Acta Neurologica Belgica, 2015)

Molecular genetics of MARVELD2 and clinical phenotype in Pakistani and Slovak families segregating DFNB49 hearing loss - Gowri Nayak; Lukas Varga; Claire Trincot; Mohsin Shahzad; Penelope L. Friedman; Iwar Klimes; John H. Greinwald; S. Amer Riazuddin; Ivica Masindova; Milan Profant; Shaheen N. Khan; Thomas B. Friedman; et al. (Human Genetics, 2015)

Biosynthesis and characterization of silver nanoparticles produced by Pleurotus ostreatus and their anticandidal and anticancer activities - Ramy S. Yehia; Hashem Al-Sheikh (World Journal of Microbiology and Biotechnology, 2014)

Matrix metalloproteinases and their pathological upregulation in multiple sclerosis: an overview - Mohammad A. Javaid; Mohamed-Nur Abdallah; Ahad S. Ahmed; Zeeshan Sheikh (Acta Neurologica Belgica, 2013)

Synthesis, biopharmaceutical characterization, and antimicrobial study of novel azo dyes of 7-hydroxy-4-methylcoumarin - Pravin S. Jogi; Jyotsana Meshram; Javed Sheikh; Taibi Ben Hadda (Medicinal Chemistry Research, 2013)

Parasitic Castration in Freshwater Snail Melanoides tuberculatus (Mollusca: Gastropoda) - S. L. Choubisa; Zulfiya Sheikh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Emissions of polychlorinated dibenzo-p-dioxins (PCDDs), dibenzofurans (PCDFs), and dioxin-like polychlorinated biphenyls (PCBs) to air from waste incinerators and high thermal processes in India - Neeta Thacker; Javed Sheikh; S. M. Tamane; Anil Bhanarkar; Deepanjan Majumdar; Kanchan Singh; Chatrapati Chavhan; Jitendra Trivedi (Environmental Monitoring and Assessment, 2013)

Impact of altitude and latitude on changes in temperature extremes over South Asia during 1971–2000 - J. V. Revadekar; S. Hameed; D. Collins; M. Manton; M. Sheikh; H. P. Borgaonkar; D. R. Kothawale; M. Adnan; A. U. Ahmed; J. Ashraf; S. Baidya; N. Islam; et al. (International Journal of Climatology, 2013)
South Asia covers more than 30° of latitude with weather observation stations situated from 6°N at Galle, Sri Lanka, to 36°N at Chitral in Pakistan. Moreover, the South Asian station network ranges in altitude from sea level to nearly 4000 m above sea level. This paper uses time series of 11 objectively defined indices of daily temperature extremes at 197 stations in Bangladesh, India, Nepal, Pakistan and Sri Lanka to examine the possible impacts of elevation and latitude on changes in temperature extremes over the period of 1971–2000. Trends in extreme indices are consistent with general warming only at low altitudes and latitudes. Stations at high altitudes and latitudes show both positive and negative trends in extreme temperature indices. As a notable example, the Diurnal Temperature Range (DTR), which has been known to decrease in most parts of the globe, has increasing trends over many high altitude stations in South Asia. Trends in extreme temperature indices at stations in South Asia higher than 2000 m above sea level are mostly in disagreement with those reported over the Tibetan Plateau. Observed trends at low altitude locations in South Asia suggest that these sites can generally expect future changes in temperature extremes that are consistent with broad‐scale warming. High‐elevation sites appear to be more influenced by local factors and, hence, future changes in temperature extremes may be less predictable for these locations. Copyright © 2012 Royal Meteorological Society

Grain growth rate and grain yield in relation to ADP-glucose pyrophosphorylase activity in wheat ( Triticum aestivum L. em. Thell) under normal and late sown conditions - S. Sheikh; V. Sikka; R. Behl; A. Kumar (Cereal Research Communications, 2010)

Membrane thermostability and chlorophyll fluorescence as indices of high temperature stress tolerance and performance in wheat ( Triticum aestivum L.) - S. Sheikh; R. Behl; S. Dhanda; R. Munjal (Cereal Research Communications, 2010)

The use of free and immobilized Cunninghamella elegans for removing cobalt ions from aqueous waste solutions - A. S. Abdel-Razek; T. M. Abdel-Ghany; S. A. Mahmoud; H. H. El-Sheikh; M. S. Mahmoud (World Journal of Microbiology and Biotechnology, 2009)

Contamination and impacts of new antifouling biocide Irgarol-1051 on subtropical coral reef waters - M. A. Sheikh; T. Higuchi; H. Fujimura; T. S. Imo; T. Miyagi; T. Oomori (International Journal of Environmental Science and Technology, 2009)

The Effect of Iron and Zinc Dietary Restriction of Pregnant Rats on Physical Growth of Litters - M. Shahbazi; N. Naghdi; S. Tahmasebi; M. Sheikh; N. Namvar Asl; A. Kazemnejad (Biological Trace Element Research, 2009)

Antibacterial activity of two limonoids from Swietenia mahagoni against multiple-drug-resistant (MDR) bacterial strains - A. K. M. Shahidur Rahman; A. K. Azad Chowdhury; Husne-Ara Ali; Sheikh Z. Raihan; Mohammad S. Ali; Lutfun Nahar; Satyajit D. Sarker (Journal of Natural Medicines, 2009)

Contamination by organochlorine pesticides from rivers - S. T. Imo; M. A. Sheikh; E. Hirosawa; T. Oomori; F. Tamaki (International Journal of Environmental Science and Technology, 2007)

The autosomal recessive nonsyndromic deafness locus DFNB72 is located on chromosome 19p13.3 - Quratul Ain; Sabiha Nazli; Saima Riazuddin; Ateeq-ul Jaleel; S. Amer Riazuddin; Ahmad U. Zafar; Shaheen N. Khan; Tayyab Husnain; Andrew J. Griffith; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)

Severe retinitis pigmentosa mapped to 4p15 and associated with a novel mutation in the PROM1 gene - Qingjiong Zhang; Fareeha Zulfiqar; Xueshan Xiao; S. Amer Riazuddin; Zahoor Ahmad; Raphael Caruso; Ian MacDonald; Paul Sieving; Sheikh Riazuddin; J. Fielding Hejtmancik (Human Genetics, 2007)

Autosomal recessive nonsyndromic deafness locus DFNB63 at chromosome 11q13.2–q13.3 - Shahid Y. Khan; Saima Riazuddin; Muhammad Tariq; Saima Anwar; Muhammad I. Shabbir; S. Amer Riazuddin; Shaheen N. Khan; Tayyab Husnain; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)

Role of cyanide production by Pseudomonas fluorescens CHA0 in the suppression of root-knot nematode, Meloidogyne javanica in tomato - Imran A. Siddiqui; S. Shahid Shaukat; Imtiaz Hussain Sheikh; Aly Khan (World Journal of Microbiology and Biotechnology, 2006)

Severe autosomal recessive retinitis pigmentosa maps to chromosome 1p13.3–p21.2 between D1S2896 and D1S457 but outside ABCA4 - Qingjiong Zhang; Fareeha Zulfiqar; Xueshan Xiao; S. Amer Riazuddin; Radha Ayyagari; Farooq Sabar; Raphael Caruso; Paul A. Sieving; Sheikh Riazuddin; J. Fielding Hejtmancik (Human Genetics, 2005)

UPR-independent dithiothreitol stress-induced genes in Aspergillus niger - D. A. MacKenzie; T. Guillemette; H. Al-Sheikh; A. J. Watson; D. J. Jeenes; P. Wongwathanarat; N. S. Dunn-Coleman; N. van. Peij; D. B. Archer (Molecular Genetics and Genomics, 2005)

A new locus for nonsyndromic deafness DFNB49 maps to chromosome 5q12.3-q14.1 - Khushnooda Ramzan; Rehan S. Shaikh; Jamil Ahmad; Shaheen N. Khan; Saima Riazuddin; Zubair M. Ahmed; Thomas B. Friedman; Edward R. Wilcox; Sheikh Riazuddin (Human Genetics, 2005)

Characterization of a novel rat cytomegalovirus (RCMV) infecting placenta-uterus of Rattus rattus diardii - H. S. Loh; M. L. Mohd-Azmi; K. Y. Lai; A. R. Sheikh-Omar; M. Zamri-Saad (Archives of Virology, 2003)

Nonsyndromic recessive deafness DFNB18 and Usher syndrome type IC are allelic mutations of USHIC - Zubair M. Ahmed; Tenesha N. Smith; Saima Riazuddin; Tomoko Makishima; Manju Ghosh; Sirosh Bokhari; Puthezhath S. Menon; Dilip Deshmukh; Andrew J. Griffith; Sheikh Riazuddin; Thomas B. Friedman; Edward R. Wilcox (Human Genetics, 2002)

Operant conditioning of rat H-reflex affects motoneuron axonal conduction velocity - Jonathan S. Carp; Xiang-Yang Chen; Hesham Sheikh; Jonathan R. Wolpaw (Experimental Brain Research, 2001)

Ultrastructural Observation of Nasal and Pulmonary Intracellular Pasteurella multocida A:3 in Rabbits - M.H. Al-Haddawi; S. Jasni; M. Zamri-Saad>; A.R. Mutalib; R. Son; A.R. Sheikh-Omar (Veterinary Research Communications, 2000)

Effects of GABA derivative TZ-50-2 on the autonomic nervous system - P. A. Galenko-Yaroshevskii; A. V. Uvarov; S. N. Linchenko; B. L. Popkov; Yu. P. Sheikh-Zade; I. L. Cherednik (Bulletin of Experimental Biology and Medicine, 2000)

Antiarrhythmic effects of KLN-93, dicaine, and lidocaine in neurogenic atrial fibrillation - N. B. Leonidov; P. A. Galenko-Yaroshevskii; Yu. R. Sheikh-Zade; I. L. Cherednik; S. B. Fitilev; D. S. Galygo; A. I. Khankoeva (Bulletin of Experimental Biology and Medicine, 1997)

Physical characteristics, and proximate composition of oocytes, liver and muscle of wild caught and tank-reared Macquarie perch - Melika Sheikh-Eldin; Sena S. De Silva; Trevor A. Anderson; Geoff Gooley (Aquaculture International, 1995)